Modelagem de ligações parafusadas pelo método dos elementos finitos - Paula Moura Leite Vilela (2016)
This work discusses the modeling of a complete bolted connection based on a model with one bolt connecting two or three plates. Initially, the behavior of this model with one bolt is analyzed by comparing it with existing bibliography for three different types of applied load: tension, shear and a combination of these two. This model includes all necessary considerations: contacts between the plates and the nut, head and shank of the bolt; contact between the plates, as well as friction; and pre-load on the bolt. The model also responds properly to loads parallel and perpendicular to the contact surface between the plates, including prying action effects. These calibrated models are then introduced as super-elements in empty spaces left on the full connection, through a relatively simple process using the finite element software ANSYS®. Upon filling these spaces, two complete connection models will be created: one with a group of bolts eccentrically loaded and one between two T-stubs. The results obtained with these models will be compared with current design codes. These two connection types have a practical application in the way they will be analyzed, and also as part of more complex connections: bolted girder splices (in the region of web beam), beam-tocolumn connections with splice plates or end plate connections, beam splices with end-plates, etc.